Examining the Impact of Macroeconomic Variables on the NEPSE Index: VECM Approach - Sigdel, Sahadev; Adhikari, Gyan (Journal of Kathmandu BernHardt College, 2024)
NEPSE plays a pivotal role in Nepal’s financial ecosystem, fostering economic growth, corporate development, and investment opportunities. The study of macroeconomic variables’ impact on the NEPSE Index is significant as it provides insights for investors and policymakers to make informed decisions, enhancing market efficiency and economic stability. This study examines the impact of macroeconomic variables on the NEPSE Index using secondary data from 1994 to 2023 and the VECM approach, revealing a long-run equilibrium among variables with significant influences from GDP, WTI, IR, and M2. The analysis highlights rapid adjustments towards equilibrium, negligible effects from lagged GDP and IR changes, and asymmetric causal relationships observed in Engle-Granger tests. The regression analysis shows moderate explanatory power with significant model fit indicators and reveals no residual autocorrelation or serial correlation, suggesting robustness in modeling the NEPSE Index dynamics. Recommendations include leveraging these findings for targeted policy interventions to enhance market stability and investor confidence.